(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
This paper describes a way of parallel algorithm technology usage for analyzing physical processes parabolic differential problems on the surface. This analysis determine the temperature distribution on the surface. Such analysis can fit calculation of Maxwell and Maxwell-Stokes equations and can be focused on mathematical models that can be reduced to the absorption or diffusion-convection-reaction equations with the initial and boundary conditions of different order (1st, 2nd, 3rd order of boundary conditions). Parallel computing technologies usage provides an acceleration possibilities of mentioned calculations in different way and effect depending of parallel technology type and method combinations used during the calculations.